Velopharyngeal Structural and Functional Assessment of Speech in Young Children Using Dynamic Magnetic Resonance Imaging. (July 2017) - Perry, Jamie L.; Kuehn, David P.; Sutton, Bradley P.; Fang, Xiangming
Objective: The purpose of this study was to demonstrate a novel method for examining the velopharyngeal mechanism using static and dynamic magnetic resonance imaging (MRI) at the sentence-level production in young children with normal anatomy. This study examined whether velopharyngeal events occurring in the midsagittal plane are correlated to muscle events occurring along the plane of velopharyngeal closure. Adenoid involvement in velopharyngeal function was also explored. Methods: A high-resolution, T2-weighted turbo-spin-echo three-dimensional anatomical scan was used to acquire static velopharyngeal data and a fast-gradient echo fast low angle shot multishot spiral technique (15.8 frames per second) was used to acquire dynamic data on 11 children between 4 and 9 years old. Results: Changes in velar knee height from rest to the bilabial /p/ production was strongly correlated with changes in the velar configuration ( r = 0.680, P = .021) and levator muscle contraction ( r = 0.703, P = .016). Velar configuration was highly correlated to levator muscle changes ( r = 0.685, P = .020). Mean alpha angle during bilabial /p/ production was 176°, which demonstrated that subjects achieve velopharyngeal closure at or just below the palatal plane. Subjects with a larger adenoid pad used significantly less ( r = –0.660, P = .027) levator muscle contraction compared with individuals with smaller adenoids. Conclusions: This study demonstrates a potentially useful technique in dynamic MRI that does not rely on cyclic repetitions or sustained phonation. This study lends support to the clinical potential of dynamic MRI methods for cleft palate management.